Histograma tempo/área geoprocessado: uso em modelo chuva-vazão concentrado - Maziero, Elisandra (2010)
Several rainfall-runoff methods use the synthetic time-area histogram HTA to simulate the translation effect of the watershed runoff. In those cases, the HTA can be defined by using the parameter named time of concentration (Tc). A model which automatically calculates the HTA might not consider the variation of land use, vegetation cover and further physiographic features of the basin. This fact is justified because the model uses the average conditions of the basin exactly as the concentrate model does. However, some physical aspects of the watershed change the flow velocity and the time of water flow, for instance the land slop and land use. A model that makes use of these peculiarities can appraise that, for the several aspects verified in the watershed, there are some velocity variations between the bigger and the smaller flow resistance. This paper presents a methodology which intends to obtain the HTA in a geo-processed way by evaluating the physiography and the land use in a watershed. This strict analysis will demonstrate the main steps needed to construct the map for the time of water flow according to pixel-to-pixel. The proposed methodology has presented good results, considering the didactical understanding of the processes related to the hydrology cycle and hydrology modeling.